The characteristics of chronic benzene poisoning in 176 Chinese occupational population cases - Gou, Lian; Ma, Xingyu; Huang, Lili; Qiu, Mei; Guo, Ruiqing; Jia, Jun; Xu, Peiyu; Lian, Nan (Frontiers in Public Health, 2025)
Benzene is a widespread environmental carcinogen known to induce leukemia. Chronic benzene poisoning is a significant occupational health issue in China, particularly among workers exposed to benzene. The aim of this study was to analyze the distribution patterns and trends of occupational benzene poisoning cases. This study included 176 cases who are diagnosed with occupational chronic benzene poisoning, via the Occupational Disease Direct Network Reporting System of the Sichuan Center for Disease Control and Prevention from 2005 to 2019. Data on gender, date of birth, years of benzene exposure, enterprise size, ownership type, industry were collected and descriptively analyzed. No significant differences were observed between males and females in terms of age or benzene exposure duration. The variation in gender distribution across 4 periods highlighted significant differences (χ2 = 13.06, p = 0.004). Linear regression analysis indicated that the number of workers increased with year as the independent variable (r2 = 0.40, p = 0.016). The working duration of benzene exposure appeared to decline, but this trend was not statistically significant. The majority of employees were in medium and large-sized enterprises. Before 2016, workers were mainly in joint-stock enterprises and equipment manufacturing industries; however, from 2017 to 2019, benzene poisoning cases were increasingly found in private and light industries. Overall, this study may provide data resources for risk assessment among occupational benzene-exposed workers; therefore, the monitoring of benzene concentrations in the workplace should be strengthened, and targeted preventive measures for workers must be effectively implemented to protect their health.